2018
DOI: 10.1111/str.12289
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the hidden content of layered documents by means of photoacoustic imaging

Abstract: We introduce a novel diagnostic approach for the uncovering of hidden content in layered documents, based on a photoacoustic imaging set‐up with optimised acoustic detection parameters. By exploiting the laser‐induced ultrasound following the intense absorption of pulsed optical radiation by printed ink, this traditional biomedical imaging method is proven capable of revealing text characters buried under several layers of stacked paper sheets at high spatial resolution and excellent contrast levels. Such a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…This puts various barriers to scholars and hinders their access for further investigations, urging for noninvasive analytical approaches that will allow access to the content of such historical objects without any further risk. In an attempt to address these challenges, a PA imaging methodology, similar to the detection of underdrawings in paintings, has been developed for the extraction of hidden content in layered documents [45]. In this case though, the irradiation wavelength was switched to 532 nm, to increase further the optical absorption from carbon-based inks, enhancing thus the amplitude of the generated PA waves for the applied energy fluence.…”
Section: Uncovering the Hidden Content Of Layered Documentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This puts various barriers to scholars and hinders their access for further investigations, urging for noninvasive analytical approaches that will allow access to the content of such historical objects without any further risk. In an attempt to address these challenges, a PA imaging methodology, similar to the detection of underdrawings in paintings, has been developed for the extraction of hidden content in layered documents [45]. In this case though, the irradiation wavelength was switched to 532 nm, to increase further the optical absorption from carbon-based inks, enhancing thus the amplitude of the generated PA waves for the applied energy fluence.…”
Section: Uncovering the Hidden Content Of Layered Documentsmentioning
confidence: 99%
“…Imaging depth is measured starting from the page facing the illumination side. Figure adapted from[45]…”
mentioning
confidence: 99%
“…Despite the fact that the vast majority of studies have utilized PA imaging for biomedical applications, recent works have demonstrated the remarkable potential of such technologies in artwork diagnostics. More specifically, different PA-based techniques have been employed for the visualization of hidden underdrawings in paintings [ 7 , 8 ], the uncovering of text in multilayered documents [ 9 ], as well as the thickness measurement of thin paint layers through the analysis of PA signal attenuation [ 10 , 11 ]. Nevertheless, all the presented PA diagnostic systems optimized for such applications have been strictly limited to the imaging of relatively thin objects due to the detection of signals in transmission geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the up to three orders of magnitude lower attenuation coefficient of ultrasound compared to NIR radiation, imaging depths of several mm can be achieved in turbid media with a spatial resolution determined by acoustic detection parameters rather than by focused light [10]. Such novel PA imaging approaches have already been applied in CH for the visualization of hidden underdrawings in paintings [11], the thickness measurement of paint layers [12], as well as the uncovering of content in layered documents [13].…”
mentioning
confidence: 99%
“…In this Letter, a 3% w/v CMC gel layer has been used as a highly compatible immersion medium [11] for the efficient detection of the generated PA signals. Nevertheless, in the case of sensitive paint surfaces that could not tolerate contact with any gel material, the option of immersion medium-free PA imaging could be considered by incorporating a fully non-contact interferometric ultrasonic detector, or highefficiency air-coupled transducers [13]. This Letter has provided experimental evidence that the effective combination of these two diagnostic techniques can offer highly complementary information, allowing for the accurate mapping and delineation of different stratigraphic layers in a painted artwork.…”
mentioning
confidence: 99%